Review of metazoan parasites of the northern fur seal (Callorhinus ursinus) and the analysis of the gastrointestinal helminth community of the population on St. Paul Island, Alaska - Kuzmina, Tetiana A; Kuzmin, Yuriy; Dzeverin, Igor; Lisitsyna, Olga I; Spraker, Terry R; Korol, Eleonora M; Kuchta, Roman (Parasitology research, 2021)
The northern fur seal (NFS), Callorhinus ursinus (Mammalia: Otariidae), is a marine mammal species included into the IUCN Red List as the vulnerable species which population is dramatically declining. A significant amount of parasitological data collected previously and our recent data allowed us to clarify the list of NFS metazoan parasites and to perform a comprehensive analysis of the gastrointestinal helminth community. Gastrointestinal tracts from 756 NFSs (3- to 4-year-old males) were collected during the annual Aleut subsistence harvests in July-August of 2011-2014 from five separate rookeries on St. Paul Island, Alaska. Totally, 27,625 specimens of helminths and approximately 1000 nasal mites were collected and identified. Detailed analysis of the previously published and newly obtained data revealed 32 species of metazoan parasites, including trematodes (6 species), cestodes (4), nematodes (9), acanthocephalans (9) and arthropods (4). The gastrointestinal helminth community of newly studied NFSs comprised 19 species including trematodes (4), cestodes (3), nematodes (5) and acanthocephalans (7). Temporal changes in the helminth community structure were small but statistically significant. Gastrointestinal helminth infracommunities comprised from 1 to 10 species (average of 4). Small but significant correlation was found between the abundances of acanthocephalans (Corynosoma similis and C. strumosum), nematodes (Contracaecum osculatum, Pseudoterranova spp.) and cestode Diphyllobothrium tetrapterum.
Keywords: Cestoda; Islands; Male; Fur Seals; lachtani rodu Arctocephalus a Callorhinus; Nematoda; cizopasní červi; prevalence; Gastrointestinal Tract; paraziti; Aljaška; mužské pohlaví; helmintózy zvířat; Parasite community; Marine mammals; Animals; Alaska; zvířata; Trematoda; Prevalence; gastrointestinální trakt; Helminths; Parasites; Acanthocephala; Helminthiasis, Animal; ostrovy